2017
DOI: 10.1242/jcs.197343
|View full text |Cite
|
Sign up to set email alerts
|

IKKα regulates human keratinocyte migration through surveillance of the redox environment

Abstract: Although the functions of H2O2 in epidermal wound repair are conserved throughout evolution, the underlying signaling mechanisms are largely unknown. In this study we used human keratinocytes (HEK001) to investigate H2O2-dependent wound repair mechanisms. Scratch wounding led to H2O2 production in two or three cell layers at the wound margin within ∼30 min and subsequent cysteine modification of proteins via sulfenylation. Intriguingly, exogenous H2O2 treatment resulted in preferential sulfenylation of keratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…However recent studies with cultured human keratinocytes show that in response to a scratch injury human keratinocytes also produce hydrogen peroxide in cells within 2–3 cells adjacent to the scratch, within 30 mins of injury. Interestingly, this study shows that addition of exogenous hydrogen peroxide results in detachment and migration of the keratinocytes adjacent to the scratch (Lisse et al, 2016; Lisse and Rieger, 2017). This might suggest that although this pathway is conserved cross-species that the amount produced in mammalian cells may not suffice to activate the necessary pro-regenerative down-stream pathways.…”
Section: Common Traits Of Scar-free Wound Healingmentioning
confidence: 78%
See 1 more Smart Citation
“…However recent studies with cultured human keratinocytes show that in response to a scratch injury human keratinocytes also produce hydrogen peroxide in cells within 2–3 cells adjacent to the scratch, within 30 mins of injury. Interestingly, this study shows that addition of exogenous hydrogen peroxide results in detachment and migration of the keratinocytes adjacent to the scratch (Lisse et al, 2016; Lisse and Rieger, 2017). This might suggest that although this pathway is conserved cross-species that the amount produced in mammalian cells may not suffice to activate the necessary pro-regenerative down-stream pathways.…”
Section: Common Traits Of Scar-free Wound Healingmentioning
confidence: 78%
“…For example, hydrogen peroxide is able to destabilize the phosphatase Dusp6 that allows for increased phosphorylation of Erk1/2, allowing for the activation of several downstream proteins and genes. Whilst in human keratinocytes H 2 O 2 has been shown to play an essential role in activating signaling factors like IKKα, that promotes migration through dynamic interactions with the EGF promoter depending on the redox state within cells (Lisse and Rieger, 2017)…”
Section: Common Traits Of Scar-free Wound Healingmentioning
confidence: 99%
“…49 ROS directly or indirectly activate the MAPK and NF-κB signaling pathways. [50][51][52][53][54][55][56][57][58] Previous studies demonstrated that H 2 O 2 induces reversible oxidation of cysteine residues of IKKα/ β and phosphorylation of IκBα, which subsequently activates the NF-κB signaling pathway. 54,55 ROS also induce the dislocation of Trx from apoptosis signal-regulating kinase 1 (ASK1), which then phosphorylates JNK and p38 and finally leads to activation of the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…SOD catalyzes the disproportionation of superoxide into either molecular oxygen or hydrogen peroxide as part of its antioxidant defense mechanism. Hence, SOD enzymes maintain a range of ROS in order to control potential toxicity, as well as downstream cellular and signaling functions [33]. There are three forms of SODs, and the localization of the SODs reflect their antioxidative roles within cells.…”
Section: Preventsmentioning
confidence: 99%